Current Directions in the Auricular Vagus Nerve Stimulation I – A Physiological Perspective - Kaniusas, Eugenijus; Kampusch, Stefan; Tittgemeyer, Marc; Panetsos, Fivos; Gines, Raquel Fernandez; Papa, Michele; Kiss, Attila; Podesser, Bruno; Cassara, Antonino Mario; Tanghe, Emmeric; Samoudi, Amine Mohammed; Tarnaud, Thomas; et al. (Frontiers in Neuroscience, 2019)
Electrical stimulation of the auricular vagus nerve (aVNS) is an emerging technology in the field of bioelectronic medicine with applications in therapy. Modulation of the afferent vagus nerve affects a large number of physiological processes and bodily states associated with information transfer between the brain and body. These include disease mitigating effects and sustainable therapeutic applications ranging from chronic pain diseases, neurodegenerative and metabolic ailments to inflammatory and cardiovascular diseases. Given the current evidence from experimental research in animal and clinical studies we discuss basic aVNS mechanisms and their potential clinical effects. Collectively, we provide a focussed review on the physiological role of the vagus nerve and formulate a biology-driven rationale for aVNS. For the first time, two international workshops on aVNS have been held in Warsaw and Vienna in 2017 within the framework of EU COST Action “European network for innovative uses of EMFs in biomedical applications (BM1309)”. Both workshops focussed critically on the driving physiological mechanisms of aVNS, its experimental and clinical studies in animals and humans, in-silico aVNS studies, technological advancements, and regulatory barriers. The results of the workshops are covered in two reviews, covering physiological and engineering aspects. The present review summarizes on physiological aspects - a discussion of engineering aspects is provided by our accompanying article (Kaniusas et al., 2019). Both reviews build a reasonable bridge from the rationale of aVNS as a therapeutic tool to current research lines, all of them being highly relevant for the promising aVNS technology to reach the patient.